Descentralização das ações de Vigilância Sanitária nos municípios em Gestão Plena, Estado do Rio de Janeiro Decentralization of Health Surveillance actions in cities with local health managment in the State of Rio de Janeiro - Mirian Miranda Cohen; Maria de Lourdes de Oliveira Moura; Jeane Gláucia Tomazelli (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2004)
O Centro de Vigilância Sanitária da Secretaria de Estado da Saúde do Rio de Janeiro pretende, com a descentralização das ações de vigilância sanitária para os Municípios, atender condições mínimas para fortalecer o sistema estadual de Vigilância Sanitária, criando estrutura de apoio ao processo de descentralização. Este trabalho objetiva apresentar o diagnóstico situacional dos órgãos de vigilância sanitária dos municípios em Gestão Plena do Sistema Municipal, discutindo os principais resultados. A metodologia compreende a análise dos 22 órgãos de vigilância sanitária em Gestão Plena do Sistema Municipal, conforme a Norma Operacional Básica 96, no período de julho a dezembro de 2002, através de questionário padrão aplicado pelo Centro de Vigilância Sanitária e de observação participante. Com base nos resultados, conclui-se que a maioria dos órgãos de vigilância sanitária municipais em Gestão Plena do Sistema Municipal, possuem profundas dificuldades técnico-operacionais no desenvolvimento das ações descentralizadas, denotando a fragilidade do processo de descentralização das ações de Vigilância Sanitária no Estado e a necessidade de sensibilizar os gestores para a efetiva estruturação das vigilâncias sanitárias locais, em parceria com o órgão estadual de Vigilância Sanitária. The Health Surveillance Center of the State of Rio de Janeiro intends, with the decentralization of low complexity health surveillance actions for Cities, to meet the minimum requirements to strengthen the state health surveillance system, creating a support structure for the descentraliztion process. The objective of this paper is to present the situational diagnosis of the health surveillance agencies that have adopted the System Full Management. The methodology encompasses the analysis of 22 municipal health surveillance agencies that use the System Full Management, according to the Unified Health System's Basic Operational Norm dated 01/96, in the period from July to December 2002, by means of a standard questionnaire applied by the Health Surveillance Center of the State of Rio de Janeiro, including comments of participants, in which the multiprofessional team interacted with the local services technical team during a technical visit. In addition to collecting data, the team tried to provide guidance as to information techniques and administrative organization. Based on the results, we conclued that most municipal health surveillance agencies with System Full Management have serious technical-operational difficulties in the development of decentralized actions, showing the need to make municipal managers aware of the importance of these actions and to guide them in effectively structuring local health surveillance, in a partnership with the Health surveillance Center of the State of Rio de Janeiro.